2020
DOI: 10.1080/07391102.2020.1773318
|View full text |Cite
|
Sign up to set email alerts
|

Structural and simulation analysis of hotspot residues interactions of SARS-CoV 2 with human ACE2 receptor

Abstract: The novel corona virus disease 2019 (SARS-CoV 2) pandemic outbreak was alarming. The binding of SARS-CoV (CoV) spike protein (S-Protein) Receptor Binding Domain (RBD) to Angiotensin converting enzyme 2 (ACE2) receptor initiates the entry of corona virus into the host cells leading to the infection. However, considering the mutations reported in the SARS-CoV 2 (nCoV), the structural changes and the binding interactions of the S-protein RBD of nCoV were not clear. The present study was designed to elucidate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(82 citation statements)
references
References 38 publications
3
79
0
Order By: Relevance
“…Study by Amin et al ( 2020 ) reported hACE2 receptor [E329] variant with SARS-CoV spike protein with high contribution for binding energy. Recently, a study proved that wild hACE2 receptor and SARS-CoV-2 spike protein (–35.33 Kcal/mol) are having a stable interaction and are present at the moderate zone similar to the present results (Veeramachaneni et al, 2020 ). Previous study reported that SARS-CoV-2 spike protein [G476S] variant has a significant very strong point and a strong direct binding affinity with hACE2 receptor, and similarly, the G476S variant showed strong binding [G726R] of spike and falling in the very strong zone (Korber et al, 2020 ).…”
Section: Discussionsupporting
confidence: 91%
“…Study by Amin et al ( 2020 ) reported hACE2 receptor [E329] variant with SARS-CoV spike protein with high contribution for binding energy. Recently, a study proved that wild hACE2 receptor and SARS-CoV-2 spike protein (–35.33 Kcal/mol) are having a stable interaction and are present at the moderate zone similar to the present results (Veeramachaneni et al, 2020 ). Previous study reported that SARS-CoV-2 spike protein [G476S] variant has a significant very strong point and a strong direct binding affinity with hACE2 receptor, and similarly, the G476S variant showed strong binding [G726R] of spike and falling in the very strong zone (Korber et al, 2020 ).…”
Section: Discussionsupporting
confidence: 91%
“…Based on the recent structural and MD studies, many key amino acid residues of the ACE2 receptor are identified in interacting with its partner proteins (Lan et al, 2020 ; Veeramachaneni et al, 2020 ). The human ACE2 receptor contains two hotspot residues Lys31 and Lys353.…”
Section: Resultsmentioning
confidence: 99%
“…Molecular docking of standard drugs and bioactives from medicinal plants with receptor molecules was performed using AutoDock Vina (Trott & Olson, 2010 ). The catalytic site of SARS-CoV-2 M pro (His41 and Cys145), receptor binding motif of S-protein (Leu455, Phe486, Glu493 and Ser494) and hotspot binding residues of ACE2 receptor (Lys31 and Lys353) were chosen as binding sites for docking analysis (Jin et al, 2020 ; Lan et al, 2020 ; Shang et al, 2020 ; Veeramachaneni et al, 2020 ; Yan et al, 2020 ). Grid box was generated using ADT with dimensions relative to the ligands (XYZ) with a resolution of 1 Å.…”
Section: Methodsmentioning
confidence: 99%
“…Based on the recent structural and molecular dynamics studies, many important amino acid residues of the ACE2 receptor are recognized in interacting with its partner proteins [ 8 , 45 ]. The human ACE2 receptor contains hotspot Lys31 and hotspot Lys353.…”
Section: Resultsmentioning
confidence: 99%